Influence of two different vinification procedures on the physicochemical and sensory properties of Brazilian non-Vitis vinifera red wines - Castilhos, Maurício Bonatto Machado de [UNESP]; Cattelan, Marília Gonçalves [UNESP]; Conti-Silva, Ana Carolina [UNESP]; Bianchi, Vanildo Luiz Del [UNESP] (Elsevier, 2013)
The objective of this study was to evaluate the association between the physicochemical properties and sensory acceptance of Brazilian red wines by applying chemometric techniques. Therefore, three winemaking processes were carried out: a traditional winemaking process and two novel winemaking processes, pre-drying and static pomace. Significant differences could be identified amongst the physicochemical properties of the wines (P<0.001). The sensory results showed greater acceptance of the wines made after pre-drying of the grapes or from the static pomace, as compared to commercial brands. Cluster analysis and Multidimensional Scaling were successfully applied and their results demonstrated the influence of the total phenolic content and color indexes on acceptance of the appearance of the wines. The odor was associated with the alcohol content, acidity, dry extract, total and reducing sugars and the body of the wines. The flavor was associated with several physicochemical properties which influenced the overall acceptance of the samples. © 2013 Elsevier Ltd.
Keywords: Physicochemical properties; Pre-drying; Red wine; Sensory acceptance; Static pomace; Physicochemical property; Cluster analysis; Drying; Vitaceae; Vitis vinifera